Empowering struggling readers : practices for the middle grades - Hall, Leigh A.; Burns, Leslie D.; Edwards, Elizabeth Carr. (New York : Guilford Press, 2011)
This book provides classroom-tested methods for engaging struggling middle grade readers--even those who appear to have given up--and fostering their success. The emphasis is on constructing respectful, encouraging learning environments that incorporate students' diverse literacies, cultural interests, and prior knowledge and skills into instruction. --from publisher description
Includes bibliographical references (p. 209-229) and index.
Keywords: Content area reading -- United States; Language arts (Middle school) -- United States